Do Global Value Chains Weaken the Exchange Rate Elasticity of Exports? an Application of the Time-Varying Coefficient Model on Panel Data - Mendoza, Adrian R.; Associate Professor Genelyn Ma. F. Sarte (2024)
ABSTRACT

In a typical setup of global value chains (GVCs), producers use imported inputs to manufacture their exports, which may end up as inputs to another country's exports. This intertwinning of exporting and importing in global production seems to have created a paradox wherein globalization, and GVCs in particular, dampened the sensitivity of gross trade flows to exchange rate elasticities of merchandise exports using a panel of 142 countries from 1995 to 2022. The extensive coverage of the dataset captures various degrees of GVC participation across countries, while the time span covers globally-important events such as trade liberalization, global recessions indicate a significant moderating impact of greater GVC participation on the real effective exchange rate elasticities of merchandise exports. This is mainly traced to stranger back GVC participation or the intensive use of imported inputs in exports. Time-varying coefficient (TVC) regression also confirm that the exports elasticities have progressively weakened from the 1990s to the early 2010s, which coincidence with intensive trade liberalization and the exponential rise of GVCs. But the weakening trend in export elasticities slowed down during the mid-2010s, which coincided with intensive trade liberalization and the exponential rise of GVCs. But the weakening trend in export elasticities slowed down during the mid-2010s which overlaps with disruptive events after the global financial crisis. These results suggest that the strength of export elasticities tend to negatively co-evolve with the ebb and flow of globalization, with stronger export elasticities observed when GVCs are less important and the traditional expenditure-switching mechanism dominates. The TVC regression also indicate that the moderating effect of GVCs on export elasticities is mainly driven by backward participation, while forward participation likely produced an offsetting effect.
Includes bibliographic reference.
Keywords: Global Value Chains -- Real Effective Exchange Rates -- Export Elasticities -- backward GVC partcipation -- forward GVC participation -- Globalization -- Deglobalization -- Panel Data -- Time-Varying Coefficient Model